If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + 5x = 12x + -6 Reorder the terms: 22 + 5x = -6 + 12x Solving 22 + 5x = -6 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 22 + 5x + -12x = -6 + 12x + -12x Combine like terms: 5x + -12x = -7x 22 + -7x = -6 + 12x + -12x Combine like terms: 12x + -12x = 0 22 + -7x = -6 + 0 22 + -7x = -6 Add '-22' to each side of the equation. 22 + -22 + -7x = -6 + -22 Combine like terms: 22 + -22 = 0 0 + -7x = -6 + -22 -7x = -6 + -22 Combine like terms: -6 + -22 = -28 -7x = -28 Divide each side by '-7'. x = 4 Simplifying x = 4
| 1/x-6=3/12x | | 20=-5/9w | | 6m+2-13= | | -4x-9=5x+9 | | 14x^2+34x+90=0 | | (4w-5)-(w+7)= | | 3x^2-53x+120=0 | | 2x^2+13x+14=0 | | 2y=.6(2y*y) | | y+z+6cy+6cz= | | 7x-10x=-9-12 | | M/2 | | 7x+2=5x-11 | | -20x^5+18x^4+18x^3= | | 4log(5)= | | 12x^2+39x-156=0 | | 39+(-19)+(-23)= | | 7+3s-5=8s+6 | | 9y^3-4y-45y^2+20=0 | | x*2+5x-14=0 | | (2x-3)/2 | | 8b=-10+9b | | 15%=32.50 | | 4x+x=225 | | 5t+15-6= | | t-8=10-t | | (8x^6w^3-2xw^8)/(2xw^3) | | 1/8=2/x | | x^2+1=1-2x | | F(X)=9X+3 | | 3-z=6 | | 7-3x=31-11x |